PEMBERIAN PELATIHAN TERHADAP KETERAMPILAN BRISK WALKING EXERCISE PADA LANSIA DENGAN HIPERTENSI DI KELURAHAN BUJEL WILAYAH KERJA PUSKESMAS SUKORAME KOTA KEDIRI - eva dwi ramayanti; Erik Irham Lutfi; Indah Jayani; Yeni Lufiana Novita Agnes; Susmiati Susmiati (Jurnal Abdi Masyarakat, 2021)
ABSTRACTThe elderly are individuals who are in the stage of late adulthood. The elderly have health problems, one of which is hypertension. Hypertension is a state of systolic pressure of more than 140 mmHg and a diastolic pressure of more than 90 mmHg. There are still many elderly who do not know the complementary treatment of hypertension. Brisk Walking Exercise training is a brisk walk that can help the elderly with hypertension to control blood pressure in a stable state. Implementation of Service by providing training in the form of Brisk Walking Exercise (BWE) using education and demonstration methods. From the implementation of the results, it was found that residents who took part in this training experienced an increase in knowledge related to BWE. Completed education and training are given according to the sessions and stages. Residents who take part in the training can do BWE according to what is taught. The results obtained after training more residents become skilled in practicing BWE. From the implementation of this activity, residents received education and training about BWE so that they were able to apply it daily as a preventive and rehabilitative action in handling clients with a history of hypertension in the community.Keywords: Keywords: Brisk Walking Exercise Training, Hypertension, ElderlyABSTRAKLansia merupakan individu yang berada dalam tahapan usia dewasa akhir. Lansia memiliki masalah kesehatan salah satunya yaitu penyakit hipertensi. Hipertensi merupakan keadaan tekanan sistolik lebih dari 140mmHg dan distolik lebih dari 90 mmHg. Masih banyak lansia yang belum mengetahui penanganan komplementer dari hipertensi. Pelatihan Brisk Walking Exercise merupakan berjalan kaki dengan cepat yang dapat membantu lansia dengan hipertensi untuk mengontrol tekanan darah tetap dalam keadaan stabil. Pelaksanaan Pengabdian dengan memberikan pelatihan berupa Brisk Walking Exercise (BWE) dengan menggunakan metode edukasi dan demontasi. Dari pelaksanaan hasil didapatkan warga yang mengikuti pelatihan ini mengalami peningktan pengetahuan terkait BWE. Edukasi dan pelatihan selesai diberikan sesuai dengans sesi dan tahapanya. Warga yang mengikuti pelatihan bisa melakukan BWE sesuai yang diajarkan. Didapatkan hasil setelah pelatihan lebih warga menjadi terampil mempraktekan BWE. Dari pelaksanaan kegiatan ini warga mendapat edukasi dan pelatihanÂ  tentang BWE sehingga mampu menerapkana sehari-hari sebagai upaa tindakan preventif dan rehabilitatif dalam penanganan klien dengan riwayat Hipertensi dikomunitas.Kata Kunci: Kata Kunci: Pelatihan Brisk Walking Exercise, Hipertensi, Lansia